Lorie Bursa - Carabbacan, Mary Joy M. 4 0 16; 5 (2011)
EXECUTIVE SUMMARY: NAME OF BUSINESS: Lorie Bursa is the name given for the business. It is named after the word Lorricaridae which is the family of armored catfish and Bursa which means leather bags in Medieval Latin. Lori Bursa turns the janitor fish skin into a leather bag. TYPE OF BUSINESS: Lorie Bursa will offer the market not just an ordinary leather bags. These leather bags are unique because its leather material is made out of janitor fish skins. This king of product is new to the market. DESCRIPTIVE DEFINITION OF THE BUSINESS: Lorie Bursa may appear to be an ordinary business until the market or consumers would know that the main material of the product or the bags is made out of janitor fish skin. Most of the company who sells leather bags is made out of cow hide, crocodile skin, and snake skins which are commonly used. These will serve as the uniqueness of Lorie Bursa against its competitors. Lorie Bursa those not only pertains to business but also help to solve environmental problem in Marikina regarding janitor fish which considered as a pest in the river. Lorie Bursa will turn this Problem into a profitable source of income. FINANCIAL REQUIREMENTS: The total investment will come from two owners which considered their self as partners. They are financially inclined to have an equal financial investment of five hundred thousand pesos each which will a total of one million pesos that will help the business to have full operations. MANAGEMENT: Lorie Bursa will have two capitalist partners sharing equal profits and loses of the business. The owners will be the general manager who will take over the whole operation of the business and they will have a marketing officer who's in charge in promoting and introducing the product to the market and a cashier who will collect the payments together with the sales persons that will attend to the customers who will buy the products. PROJECTED TIME TABLE: The proposed business will commence after 6 months of preparation, study and acquisition. The first 2 months will be used in conciuding the study. The next month is allotted for the application and compliance of legal requirements and registration. One month will utilize in the development and design of business location. The acquisition of the equipments, recruitment and hiring of personnel will be done simultaneously for one month prior to opening. The publicity and promotions will begin one month before the commencement of the business until it becomes fully-operational.
Business Plan: (BSBA major in Management) - Pamantasan ng Lungsod ng Maynila, 2011.
Keywords: 2 -- 0; 6; 20; 20; 2